Impact of Green Marketing Mix on Purchase Behavior of Environmentally Conscious Consumers of Kathmandu Valley in Fashion Industry - Phuyal, Sanskriti; Neupane, Kritika; Timilsina, Urja Shree; Silwal, Sneha; Khadka, Dipjal Kumar (New Perspective: Journal of Business and Economics, 2025)
The growing environmental awareness has significantly influenced the business men to adopt strategies which resemble consumer’s mindset towards environmental awareness, especially in the fashion industry. The study aims at measuring the impact of green marketing mix on the purchase behavior in Kathmandu focusing on the fashion industry for consumers who consider eco friendliness of aa apparel in the environment. The study followed a quantitative approach. With the use of a survey questionnaire, 110 respondents participated in this study. The study applied descriptive statistics, correlation, ANOVA and regression analysis. IBM SPSS software was used to analyze the model. The study examined four factors that impacted the purchase behavior of environmentally conscious consumers in the Fashion industry in Kathmandu Valley: green product, green place, green price and green promotion. The study finds that two factors, green product and green place have significant positive impact on the purchase behavior of environmentally conscious apparel consumers in Kathmandu Valley. On the contrary, green price and green promotion was found to have no significant impact on the purchase behavior. The study will help fashion brands and retailers understand the concept of green marketing mix and formulate marketing strategies effectively. Future research can explore other factors like green people, green process and green physical evidence in the context of the other industries as well as in other parts of Nepal.